The influence of profitability and growth on dividend policy with firm size as a control variable in the oil and gas subsector listed on the Indonesian Stock Exchange for the 2020-2024 period - Riyandi Riyandi; Hari Sulistiyo; Irvan Yoga Pardistya (Universitas Nusa Cendana, 2026)
This study aims to analyze the effect of profitability and company growth on dividend policy, with firm size as a control variable, in oil and gas subsector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employs a quantitative research approach using secondary data obtained from annual reports and applies logistic regression analysis. The findings indicate that profitability and company growth simultaneously affect dividend policy. Partially, profitability has a significant effect on dividend policy, whereas company growth does not have a significant effect. Furthermore, the results show that the independent variables explain 40.4% of the variation in dividend policy. These findings suggest that companies with higher profitability are more likely to distribute dividends, while company growth is not a primary consideration in determining dividend policy. Keywords: Profitability; Growth; Firm Size; Dividend Policy